MIGRASI PENDUDUK DAN PEMBENTUKAN HIBRIDITAS BUDAYA KULINER TRADISIONAL PENGKANG - Humaedi, M. Alie; Purwaningsih, Sri Sunarti (Balai Pelestarian Kebudayaan Wilayah X, 2019)
The phenomenon of population migration has been going on for a long time on socio-economic or power factors. The formation of distribution production and kinship networks due to the marriage of various tribes occurred in migration centers, including cultural hybridity. One form of cultural hybridity is the practice of traditional culinary production of pengkang in Mempawah. The problem is how the character of hybridity in creative production of pengkang culinary is done along with cultural encounters due to the migration patterns of several ethnic groups. This ethnographic research is based on the disclosure of the culinary pioneer family profile through in-depth interviews and participation observation of various hybridity phenomena. This study succeeded in finding a correlation between migration of people from various ethnic groups: Malay, Bugis, Madura, and Chinese in kinship networks and the formation of traditional culinary hybridity characters of pengkang. This culinary hybridity can be seen in the taste, producting or presentation of pengkang packaged from the Malay tradition, reinforced by the adaptation of taste and choice of ingredients known in the traditions of the Chinese, Madurese, and Bugis communities.